2021
DOI: 10.1038/s41419-021-03413-4
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA SNHG1 and RNA binding protein hnRNPL form a complex and coregulate CDH1 to boost the growth and metastasis of prostate cancer

Abstract: The interaction between LncRNA and RNA-binding protein (RBPs) plays an essential role in the regulation over the malignant progression of tumors. Previous studies on the mechanism of SNHG1, an emerging lncRNA, have primarily focused on the competing endogenous RNA (ceRNA) mechanism. Nevertheless, the underlying mechanism between SNHG1 and RBPs in tumors remains to be explored, especially in prostate cancer (PCa). SNHG1 expression profiles in PCa were determined through the analysis of TCGA data and tissue micr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…For example, the lncRNA HOTAIR has been found highly expressed in primary breast tumors and metastases, promoting cancer progression ( Gupta et al, 2010 ), while Second Chromosome Locus Associated with Prostate-1, LINC00913 , tends to be a promising biomarker given that its expression level is independently related to poor prognosis ( Prensner et al, 2013 ). In our previous study, SNHG1 has also been proved to be a novel lncRNA, contributing to the malignant progression in PCa ( Tan et al, 2021 ). Previously, methylation of 5-cytosine at the post-transcriptional level was found only in tRNAs and rRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lncRNA HOTAIR has been found highly expressed in primary breast tumors and metastases, promoting cancer progression ( Gupta et al, 2010 ), while Second Chromosome Locus Associated with Prostate-1, LINC00913 , tends to be a promising biomarker given that its expression level is independently related to poor prognosis ( Prensner et al, 2013 ). In our previous study, SNHG1 has also been proved to be a novel lncRNA, contributing to the malignant progression in PCa ( Tan et al, 2021 ). Previously, methylation of 5-cytosine at the post-transcriptional level was found only in tRNAs and rRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…45 Recently, the involvement of RBPs in gene expression and its regulation by lncRNAs has been revealed. 46,47 qRT-PCR results, we identified that both NBPF4 and EZH2 are bound and regulated by RNA binding protein ZFP36. ZFP36 is an RBP associated with tumorigenesis and is involved in transcription regulation and RNA processing.…”
Section: Discussionmentioning
confidence: 89%
“…Further, RBPs are also considered to be important regulators in gene expression 45 . Recently, the involvement of RBPs in gene expression and its regulation by lncRNAs has been revealed 46,47 . For example, overexpression of ZFP36 can reverse the upregulation of EZH2 caused by shNBPF4 and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Celf1 acts as a Cdh1 repressor and Elavl1 acts as a translational derepressor ( Yu et al, 2016 ). A recent study in human prostate cancer cells implicated another RBP, hnRNPL, in the post-transcriptional regulation of Cdh1 via modulation of Cdh1 transcript stability ( Tan et al, 2021 ). Interestingly, Elavl1 directly interacts with hnRNPL in rat hepatocytes to stabilize inducible nitric oxide synthase transcripts in response to inflammatory stimuli ( Matsui et al, 2008 ).…”
Section: Implication Of Rna-binding Proteins In Mrnas Poised For Translation Transcriptional Priming and Production Of Basal Progenitorsmentioning
confidence: 99%